Incidental finding of heterotopic supradiaphragmatic liver. Issue 10 (17th October 2020) - Jhamb, Shaurya; Pillai, Harshil; Maguire, Christopher; Palamuthusingam, Pranavan
Abstract: Here we describe a case of heterotopic, supradiaphragmatic liver in a 65-year-old woman who was referred for investigation of a soft tissue gallbladder mass. Contrast-enhanced magnetic resonance imaging revealed adenomyomatosis of the gallbladder and supradiaphragmatic accessory liver tissue. This is a remarkably rare normal variant.